PERKEMBANGAN DAN KEMUNDURAN PERDAGANGAN LADA DI ACEH ABAD 19 - Lailatusysyukriyah Lailatusysyukriyah Lailatusysyukriyah; Hartutik Hartutik (Program Studi Pendidikan Sejarah - Universitas Samudra, 2017)
Indonesia archipelago is well known by the spice production and maritime trade for many times. The best product of spice from western Indonesia archipelago is pepper that produced from the coastal line of Aceh. There were many ports that connecting international pepper trade. The purpose of research is enriched the historiography study of international spice commerce in Indonesia on the last century that connected by shipping. Spice shipping transportation system is pointing out the great expansion of maritime trade in ancient Indonesia archipelago. History methods of the research are divided by four process, heuristic, sources critics, interpretation, and historiography. The development pepper trade in Aceh on 19th century is simultaneously with the rise of international commerce in the first half 19th marked by expansion of the new networks, the flourishing of pepper production, and connection between Aceh and British Malayan in Penang. The decline pepper trade in Aceh on the last of 19th century is caused by the changing of market demand to the article that discharging of the value. Dutch expansion and military blockade in some pepper ports in Aceh, also influence on the process of decline.